Environmental regulation, technological innovation and energy consumption---a cross-region analysis in China - Liu, Yulin; Li, Zhihui; Yin, Xingmin (Journal of cleaner production, 2018)
China has encountered the environmental issues and energy pressures in the middle-income stage. Strengthening environmental regulation is a crucial measure to prevent environment deterioration and energy dilemma. This paper investigates the three types of environmental regulations on energy consumption using feasible generalized least squares method during 1997–2015 in direct and indirect path. The main conclusions are as follows. In the direct path, the economical and supervised types of environmental regulations have inhibited energy consumption whilst legal environmental regulation has no significant impact. As for indirect path, the "rebound effect" of energy is greater than the energy conservation generated by technological innovation, which is embodied as an inhibitory effect. The effects of environmental regulation display regional difference. The legal and supervised types of environmental regulations have significant "cost effect" and "rebound effect" on energy consumption in the entire samples. On the contrary, the economical environmental regulation shows the opposite sigh in eastern regions. The counterfactual simulation results show that the net effects of environmental regulations on energy consumption are negative, which is beneficial for relieving energy pressures. Based on the findings, this paper provides pertinent policy implications. [Display omitted] •Environmental regulation can be divided into three types.•Environmental regulation can affect energy consumption in direct and indirect path.•Differernt types of environmental regulation have distinct impacts on energy consumption.•The effect of environmental regulation displays regional difference.•Strengthening environmental regulation can relieve energy pressure.